1998
DOI: 10.1046/j.1570-7458.1998.00345.x
|View full text |Cite
|
Sign up to set email alerts
|

Instar‐dependent hemocyte changes in Pieris brassicae after parasitization by Cotesia glomerata

Abstract: Cotesia glomerata L. (Hymenoptera: Braconidae) is a parasitoid of early instar larvae of Pieris brassicae L. (Lepidoptera: Pieridae). Late instars of P. brassicae can more often overcome parasitization by hemocytic encapsulation of C. glomerata eggs. Short-term hemocyte responses to parasitization were examined in third and fourth instar larvae of P. brassicae. Total and differential hemocyte counts did not differ between parasitized and unparasitized host larvae. A rapid, but temporary decrease of total hemoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 22 publications
2
12
0
Order By: Relevance
“…In general, THC increases with the larval age reaching a maximum in pre‐pupae although THC also tends to increase prior to each molt, decrease at molting, and then increase again . Other studies have reported the same effect of parasitism on THC . When comparing both scenarios, we observed that parasitism was the factor which has most contributed to S. littoralis total mortality.…”
Section: Discussionsupporting
confidence: 50%
“…In general, THC increases with the larval age reaching a maximum in pre‐pupae although THC also tends to increase prior to each molt, decrease at molting, and then increase again . Other studies have reported the same effect of parasitism on THC . When comparing both scenarios, we observed that parasitism was the factor which has most contributed to S. littoralis total mortality.…”
Section: Discussionsupporting
confidence: 50%
“…1992), D. saccharalis (Barduco et al 1988;Bombonato and Gregorio, 1995;Falleiros et al, 2003), Lacanobia oleracea (Richards and Edwards, 1999). Our results are similar to those observed by Silva et al (2002), who reported the absence of quantitative alterations of OE in response to pathogens in the hemocoel of A. obliqua larvae and are discordant to Bauer et al (1998), who reported the increase of this cellular type in larvae of P. brassicae parasited by Cotesia glomerata. However, this species is a parasitoid and we worked with a virus that might have led to the different results.…”
Section: Resultssupporting
confidence: 87%
“…Hemocyte spreading defects are believed to reflect parasitemediated immunosuppression (Noda & Loker 1989;Loker et al 1992;Loker 1994). Parasitoid larvae also alter the spreading ability of hemocytes of their insect hosts (Bauer et al 1998;Beckage 1998;Stettler et al 1998). Of the hemocytes of B. glabratn observed to round, most (81%) first showed at least one calcium transient.…”
Section: Discussionmentioning
confidence: 99%